Perancangan Sistem Informasi Buku Tamu Pada Website Kantor Pencarian Dan Pertolongan Kelas A Medan - Fitri rahya Yanti; Yunita dana yanti Br Purba; Heri Santoso (LKP KARYA PRIMA KURSUS, 2024)
Abstract The Medan Class A Search and Rescue Office is a government agency whose main task is to carry out rescue, search and rescue operations. This agency is also a bridge for coordination with other agencies to improve the evacuation process in certain circumstances. An agency visit often occurs to this agency. Visitors or guests are often recorded in a special agenda or book which is recorded conventionally. This condition is certainly less effective because recording is still carried out using physical books which are easily damaged and often cause queues when guests register themselves. After knowing this problem, the author designed a guest book information system which was intended to fill in the features on the Medan Class A Search and Relief Office website. The goal is to fill in guest data more neatly and not cause data loss or damage. The method used in this research is the waterfall method, this method has its own specifications, so that a system can be developed according to what is desired. The way this method works is systematically and gradually so that all information and results will be recorded well and distributed accurately and quickly. The system was built using the PHP programming language with MySQL as the database.